2012
DOI: 10.3109/02713683.2012.678544
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis and Biochemical Correlations of Oxidative Stress Responsive Genes in Retinoblastoma

Abstract: The study suggests active involvement of redox signaling pathways in the pathogenesis of RB. Consideration of oxidative stress components in the clinical management of RB patients is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The mechanisms underlying the increase of JAKs and STATs expression under choline deficiency are unknown but might be partially related to the increased reactive oxygen species (ROS). In human retinoblastoma cells, H 2 O 2 , one important ROS induced the expression of JAK3 and STAT4 genes [47]. Our unpublished data showed that choline deficiency increased the ROS levels in the intestine of Jian carp, which supported the hypothesis.…”
Section: Choline Deficiency Induced Inflammation and Regulated Nf-κb And Stat Signaling Molecules In The Intestine Of The Fishsupporting
confidence: 71%
“…The mechanisms underlying the increase of JAKs and STATs expression under choline deficiency are unknown but might be partially related to the increased reactive oxygen species (ROS). In human retinoblastoma cells, H 2 O 2 , one important ROS induced the expression of JAK3 and STAT4 genes [47]. Our unpublished data showed that choline deficiency increased the ROS levels in the intestine of Jian carp, which supported the hypothesis.…”
Section: Choline Deficiency Induced Inflammation and Regulated Nf-κb And Stat Signaling Molecules In The Intestine Of The Fishsupporting
confidence: 71%
“…In addition, the same changes in cadherin-mediated cell adhesion correlate with the invasive properties of the human retinoblastoma cell lines isolated decades ago, providing a molecular mechanism for these earlier observations" [18]. In another study, it was seen that relating the RB gene expression with the clinico-pathologic features of the tumor tissues, and found that the tumor with invasion of choroid, optic nerve and retinal pigment epithelium, had relatively higher gene expression, when compared with the tumor with only choroidal invasion [19].…”
Section: Discussionmentioning
confidence: 93%
“…Oxidative stress via excess ROS plays a key role in the initiation and progression of carcinogenesis including retinoblastoma. 15 18 Aerobic organisms including mammals generate ROS as part of normal aerobic metabolism, and have developed elaborate antioxidant mechanisms for combating oxidative stress. The effective antioxidant defense systems for combating the toxicities of ROS is a family of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%